PERAN PERSEPSI SISWA TERHADAP BIAYA PENDIDIKAN DAN DAMPAKNYA PADA MOTIVASI BELAJAR - Anjeli Anjeli; Nuril Fuadati; Khafid Ismail (CV. Denasya Smart Publisher, 2025)
This study aims to examine students’ perceptions of educational costs and their impact on learning motivation. Educational expenses are often perceived differently among students, either as a financial burden or an investment in the future. These differing perceptions influence students’ attitudes, interest, and level of motivation. This research employs a qualitative approach using a literature review method that synthesizes approximately twenty national scholarly articles published between 2015 and 2025. Data were analyzed through narrative synthesis to identify patterns explaining the relationship between cost perceptions and learning motivation. The findings indicate that students’ perceptions of educational costs are shaped by family economic conditions, prior educational experiences, information about educational benefits, and environmental support. A high-cost perception tends to generate psychological pressure and reduce learning motivation, whereas viewing educational expenses as an investment encourages students to strive for better academic achievement. Furthermore, both intrinsic and extrinsic motivation act as reinforcing factors; a balanced combination of these motivations enhances persistence, engagement, and academic outcomes. The review also highlights that factors such as educational service quality, parental support, and scholarship availability may mediate the influence of cost perceptions on motivation. This study concludes that positive perceptions of educational costs play a crucial role in supporting learning success, emphasizing the importance of equitable financial policies and institutional strategies to strengthen student motivation.